Analisis Pengaruh Career Management, Training Satisfaction, Pay Satisfaction Terhadap Turnover Intention dan Peran Mediasi Organizational Engagement Pada Karyawan Sektor Perbankan - Budi Artiningrum; Aryana Satrya (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2016)
The purpose of this research is to understand and analyze the effects of career management, training satisfaction, pay satisfaction to employee turnover intention in the banking sector. A total of 265 respondents who work in the Commercial Bank participated, with structural equation modeling as data processing method. As a result, it was found that direct career management has no effect on turnover intention. While training proved satisfaction can affect turnover intention through full mediating role of organizational engagement. This research also found that organizational engagement provides partial mediating role in the relationship between pay satisfaction and turnover intention. Thus, this study was able to prove the importance of the role of training satisfaction and pay satisfaction in improving organizational engagement, which in turn can reduce turnover intention of employees in the banking sector. The results of this study showed that companies that have a good career management can necessarily encourage employees to stay, the phenomenon of war for talents is one of the triggers of employees interested in moving. So the company needs to formulate good strategy of career management to nurture employee engagement, for example, with the function of coaching and mentoring.